Effects of Aging on Metabolic Characteristics of Human B Cells. (1st February 2022) - Frasca, Daniela; Pallikkuth, Suresh; Pahwa, Savita
Abstract: Metabolic changes represent the most common sign of aging and lead to increased risk of developing diseases typical of old age. Age-associated metabolic changes, such as decreased insulin sensitivity, decreased mitochondrial function, and dysregulated nutrient uptake, fuel the low-grade chronic systemic inflammation, known as inflammaging, a leading cause of morbidity and mortality, linked to the development of several diseases of old age. How aging affects the metabolic phenotype of immune cells, and B cells in particular, is not well known and is under intensive investigation by several groups. In this study, we summarized the few published results linking intrinsic B-cell metabolism and B-cell function in different groups of young and elderly individuals: healthy, with type-2 diabetes mellitus, or with HIV infection. Although preliminary, these results suggest the intriguing possibility that metabolic pathways can represent potential novel therapeutic targets to reduce inflammaging and improve humoral immunity.